Localization Of The Impacted Mandibular 3rd Molar And Its Relationship To Inferior Alveolar Canal By Use Cone Beam Tomography (CBCT) In CoparisimWith OPG - ABDULKADER, SAHAR; ABAAS, WETHAQ MOHAMMED; PHADHIL, REEM; DAWOOD, AHMED ALAA (International Journal of Psychosocial Rehabilitation, 2020)
Background:This study was undertaken to evaluate the relationship between the mandibular third molar and the mandibular canal by Cone-Beam Computed TomographyCBCT and OrthoPantomo Graph OPG before surgical procedure of impacted lower wisdom . Materials and Methods:20 patients (14 women and 6 men, 18-35 years of age)(34 mandibular wisdom teeth) with preoperative panoramic radiographs suggesting close relationship with theInferior Alveolar Nerve (IAN). The Panoramic radiographs weretaken with Kodak 8000C and the cone-beam computedtomography (CBCT) were taken using a Kodak 9500C 3D conebeam system. The exposure factors were set at 120kV, and theslice thickness of contiguous sections was 1mm. Results:Panoramic radiographs suggested 34 teeth 14 women and 6 men, 18-37 years of age, and the number of teeth they in close relationship With IDN Vertical relationship between the mandibular third molar root and the mandibular canal in these teeth was 19(42.55%) withthe root apex at the upper half of the mandibular canal, 7(38.29% ) withthe root apex at the lower half of the mandibular canal and 4(19.14%) the root apex under the inferior wall of the mandibular canal. the Locations of the mandibular canal in relation to the mandibular third molars as demonstrated by CBCTin the included cases were: 6(17.02%) mandibular canals were in the buccal position, 15(44.68%) were in the inferior position, 8(23.4%) were lingual, and 5(14.89%) were between the roots Conclusion:Cone Beam Computed Tomography provides useful informationregarding the 3-dimensional relationship between the mandibularthird molar and the mandibular canal.it helps the surgeon for the planning of the surgery to avoid injury to the nerve and minimize the complications .